Dielectric and piezoelectric properties of 2-2 PZT-portland cement composites - Chaipanich A. (2014)
Piezoelectric composites made from lead zirconate titanate (PZT) and cement are developed as sensors in smart concrete structures due to its compatibility to the host structure concrete. In this work, PZT ceramic-Portland cement composites of 2-2 connectivity were produced using a dice and fill method and their dielectric and piezoelectric properties are reported. The piezoelectric coefficients, d 33, value of the 2-2 PZT-cement composite at PZT volume content of 60% and 70% are 99 pC/N and 113 pC/N respectively which are noticeably higher than that of previously tested 0-3 PZT-cement composites. The dielectric values in 2-2 composites are also higher than that of previously tested 0-3 composites. © 2013 Copyright Taylor and Francis Group, LLC.